1997
DOI: 10.7863/jum.1997.16.9.587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sonography, sonohysterography, and hysteroscopy for evaluation of abnormal uterine bleeding.

Abstract: We compared transvaginal sonography, sanahysterography, and diagnostic hysteroscopy in the evaluation of abnormal uterine bleeding. Sixtyeight women 40 or older with abnormal uterine bleeding were assigned to undergo either transvaginal sonography or sonohysterography. All subjects then had diagnostic hysteroscopy and endometrial biopsy. Patients with abnormal findings underwent operative hysteroscopy or definitive therapy. Transvaginal sonography, sonohys-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 2 publications
2
40
1
4
Order By: Relevance
“…In contrast, in 1997 Saidi MH et al, showed that transvaginal echography and sonohisterography have higher sensitivity (95% and 90%) than diagnostic hysteroscopy (78%) (11).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in 1997 Saidi MH et al, showed that transvaginal echography and sonohisterography have higher sensitivity (95% and 90%) than diagnostic hysteroscopy (78%) (11).…”
Section: Discussionmentioning
confidence: 95%
“…24 Several studies have shown that SH offers better visualization of the uterine cavity than conventional TVS and is a useful method for evaluating possible endometrial pathologic conditions. [16][17][18][19][20] However, few have attempted to address the application of SH in preoperative evaluation of endometrial cancer because of its potential risk of malignant cell dissemination into the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SH has diagnostic accuracy similar to that of hysteroscopy and is effective in assessment of dysfunctional uterine bleeding, infertility, and endometrial lesions such as polyps and submucous myomas. [16][17][18][19][20] However, SH is not widely used in preoperative evaluation for endometrial cancer because of few data to support its diagnostic accuracy and a concern about the potential risk of peritoneal spillage of malignant cells through the fallopian tubes. A prospective study showed that SH had diagnostic accuracy of 84.37% in evaluation of the depth of myometrial invasion, and the occurrence rate of malignant cells on cytologic analysis of peritoneal fluid was 6.25%.…”
mentioning
confidence: 99%
“…This approach is comparable to hysteroscopy for the detection of intrauterine lesions such as polyps and submucous leiomyomas 48,49 (Class 3). However, in the context of acute uterine bleeding, the results of contrast sonography are frequently difficult to interpret because the clot and debris existing in the endometrial cavity preclude its use in the acute setting.…”
Section: Contrast Sonographymentioning
confidence: 96%